Regulation of blood-screening in vitro diagnostics in sub-Saharan African countries remains a challenge - Abdurrahman, Goran; Samukange, Washington; Lyoko, Nyambe; Shonhiwa, Negus Onai; Kafere, Chancelar; Nübling, C. Micha; Peeling, Rosanna W.; Reinhardt, Jens (Frontiers in Medicine, 2023)
According to the World Health Organization, blood must be screened for major transmitted infections before transfusion to prevent the possibility of passing an infection to the recipient. For accurate detection of infectious disease pathogens in the blood of donors, in-vitro diagnostic medical devices (IVDs) of high specificity and sensitivity should be used. In mature healthcare systems, the regulatory authorities authorize the usage of devices with the highest performance capabilities, which are also controlled through active market oversight. However, in Sub-Saharan African countries, the regulation of IVDs is often poorly developed. With the lack of stringent regulatory oversight, IVDs of poor quality can be put on the market and used for blood donor screening, which, ultimately, poses a great public health threat. The BloodTrain is a humanitarian project from the Germany Federal Ministry of Health that aims to help strengthen the regulatory authorities in Sub-Saharan partner countries. Here, we present the status of IVD regulation in the partner countries and the objectives that the BloodTrain project aims to achieve in the region towards regulating IVDs.